Synthesis of uncapped silver nanoparticles using DC arc plasma technique: effect of change in plasma gas on morphological properties. (18th August 2010) - Shinde, Manish D.; Pawar, Amol U.; Karmakar, Soumen; Seth, Tanay; Raut, Varsha; Rane, Sunit; Das, A.K.; Bhoraskar, Sudha; Amalnerkar, Dinesh
Uncapped silver nanoparticles were synthesised using hitherto unexplored DC arc thermal plasma technique using Ar, He and mixture of Ar and He as plasma gases. Effect of change in plasma gases on the morphological properties of synthesised nanoparticles has been studied. XRD revealed formation of phase pure cubic silver. TEM study disclosed formation of nanoparticles with size in the range of 20-50 nm and 5-30 nm for silver nanopowders synthesised with He and Ar as plasma gases, respectively while a bimodal size distribution with sizes ranging from ∼20 nm to 150 nm is observed for silver nanopowders synthesised with mixture of He and Ar as plasma gases in 2 : 3 ratio. UV-visible spectroscopy results also support the wide particle size distribution. Demixing effect is presumably responsible for increase in particle size and wide variation in particle size distribution in case of nanoparticles synthesised using mixed gas plasmas.